Preparation method and application of hydrophobic supported catalyst

By hydrophobic modification and Cu-ZnO support on the surface of γ-Al2O3 material, the problem of the mesoporous structure of alumina is easily collapsed in the methanol reaction of carbon monoxide and carbon dioxide co-hydrogenation, the selectivity and stability of the catalyst are improved, and the life of the catalyst is extended.

CN119633821APending Publication Date: 2025-03-18KUNMING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411734292.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The mesoporous structure of alumina is prone to collapse in the methanol reaction of carbon monoxide and carbon dioxide co-hydrogenation, and its strong hydrophilicity leads to adverse desorption of water, affecting catalytic activity and stability.

Method used

The hydrophobicity of the γ-Al2O3 material is improved by hydrophobic modification of organic hydrophobic groups, and a γ-Al2O3 catalyst with high hydrophobicity was prepared. Cu-ZnO loading was performed using evaporation-induced self-assembly (EISA) method, wet impregnation method or easy impregnation-capture method.

Benefits of technology

It improves the methanol selectivity and reaction stability of the catalyst, extends the life of the catalyst, enhances the performance of the catalyst, and maintains high efficiency activity especially under high humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633821A_ABST
    Figure CN119633821A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of methanol through hydrogenation, in particular to a preparation method and application of a hydrophobic supported catalyst, and the preparation method comprises the following steps: S1, preparing a mesoporous gamma-Al2O3 carrier by adopting an evaporation-induced self-assembly method; s2, carrying out hydrophobic modification on the gamma-Al2O3 carrier by adopting a method of heating in a water bath kettle at a constant temperature and a low temperature and adopting silane reagents such as dimethyl diethoxy silane, propyl trimethoxy silane, octyl trimethoxy silane and the like; s3, loading Cu and ZnO by adopting a wet impregnation method or an easy impregnation-capture method; the surface property of the gamma-Al2O3 material is improved through hydrophobic modification of a methyl group, and the catalyst prepared by the method has higher hydrophobicity and has higher methanol selectivity and reaction stability compared with an unmodified catalyst in the reaction of synthesizing methanol through co-hydrogenation of carbon monoxide and carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogenation to methanol, and in particular to a preparation method and application of a hydrophobic supported catalyst. Background Art

[0002] Methanol, as an important part of the carbon dioxide conversion products, can be used as an energy carrier and as an intermediate raw material for many chemical products. 2 The catalyst for producing methanol by hydrogenating raw materials has important practical significance.

[0003] In catalytic reactions, efficient catalysts need to have high catalytic activity, good selectivity and long service life. Alumina-supported catalytic materials not only have these characteristics, but also have high mechanical strength and relatively low price, and are considered to be important catalyst carriers. Under different treatment conditions, alumina will present different crystal phases, different specific surface areas, pore structures and surface types. Among them, γ-Al with a mesoporous structure 2 O 3 The material is a better choice for catalyst carrier. 2 O 3 The material has a large specific surface area, pore volume and pore size, which can provide support space for high-load active components and provide suitable pores for catalytic reactions. 2 O 3 The material also has good chemical stability to resist the damage to the catalyst pore structure by corrosive components. At present, there is relatively little research on the preparation of high-purity alumina catalytic carrier materials in my country. Some high-end products rely on imports and cannot meet the domestic market demand. As the catalytic industry gradually develops in the direction of high efficiency and greenness, the quality requirements for catalytic products are getting higher and higher. Single-component high-purity alumina materials cannot meet certain specific catalytic performance requirements. Therefore, it is necessary to modify the surface of alumina materials so that they have unique physical and chemical properties to meet the catalytic performance requirements of special reactions in order to broaden the scope of application of catalysts.

[0004] During the process of hydrogenation of carbon monoxide and carbon dioxide to synthesize methanol, a large amount of water will be generated, which will cause the collapse of the mesoporous structure of alumina, and the specific surface area and pore volume will become smaller. In addition, the most important thing is that the alumina material is highly hydrophilic, which is not conducive to the desorption of water, and thus has an adverse effect on the activity and stability of the hydrogenation to methanol reaction. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of a hydrophobic supported catalyst, and to improve the γ-Al 2 O 3The surface hydrophilicity and hydrophobicity of the material, the catalyst prepared by the method described in the present invention has high hydrophobicity, and in the reaction of synthesizing methanol by co-hydrogenation of carbon monoxide and carbon dioxide, it has higher methanol selectivity and reaction stability compared with the unmodified catalyst.

[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0007] A method for preparing a hydrophobic supported catalyst comprises the following steps:

[0008] S1: P123 was dissolved in anhydrous ethanol, stirred evenly, and a certain amount of aluminum isopropoxide was added after adjusting the pH. After the solution was stirred into a gel state, it was dried, calcined, and sieved to obtain γ-Al with a mesoporous structure. 2 O 3 Precursor;

[0009] S2: The γ-Al obtained in step S1 is 2 O 3 The precursor is mixed with deionized water, stirred evenly at room temperature, and a hydrophobic modifier is added dropwise in a fume hood to form a mixed solution; after stirring evenly, the mixed solution is placed in a 60°C water bath and stirred; the mixed solution is mixed and stirred under the condition of a water bath, and after being fully mixed evenly, centrifuged and dried to obtain a γ-Al with a hydrophobic surface. 2 O 3 Precursor;

[0010] S3: hydrophobically modified γ-Al obtained in step S2 2 O 3 The precursor is mixed with copper nitrate trihydrate and zinc nitrate hexahydrate, and Cu-ZnO is loaded by a wet impregnation method or an easy impregnation-capture method to obtain a hydrophobic loaded catalyst.

[0011] Furthermore, the step S1 specifically comprises: synthesizing highly ordered mesoporous γ-Al by using an evaporation induced self-assembly (EISA) method 2 O 3 carrier, pluronic P123 (molecular weight 5800, EO 20 PO 70 EO 20 , Sigma-Aldrich) was stirred in ethanol solvent for 3 h, and then concentrated nitric acid solution (HNO 3 , Junsei) to make the solution acidic and continue stirring at room temperature for 3 h. 3 H 7 ) 3, Junsei) was added to the above solution and stirred vigorously at room temperature until the solution was in a gel state. The mixed gel solution was placed in a 60°C oven and dried for 48 hours to turn the gel solution into white particles. After the sample was finely ground, it was placed in a muffle furnace for calcination. When the sample cooled to room temperature, the sample was ground to ensure that the particle size of γ-Al2O3 was 60 to 90 microns. 2 O 3 powder.

[0012] Furthermore, the amount of P123 used is 4-8 g; the amount of anhydrous ethanol used is 80-160 mL; and the amount of aluminum isopropoxide used is 0.05-0.07 mol.

[0013] Furthermore, the calcination conditions are: in an air environment, heating the temperature to 400° C. at a heating rate of 1° C. / min for 4 h, and heating the temperature to 800° C. at a heating rate of 5° C. / min for 1 h.

[0014] Further, the step S2 specifically comprises: adding 1-3g γ-Al 2 O 3 The precursor was placed in a beaker containing 240 ml of deionized water, and a certain amount of hydrophobic modifier was added. The mixture was stirred at room temperature for 30 min to make the γ-Al 2 O 3 The particles were evenly dispersed. Stirring was performed in a water bath at 60°C for 5 hours. During stirring, the beaker mouth should be sealed to prevent water vapor from entering. After stirring, the solution was centrifuged at a speed of 3500r / min, and the carrier was washed three times with anhydrous ethanol. After centrifugation, the supernatant was filtered and the powder was placed in a 60°C oven for 24 hours to obtain hydrophobically modified γ-Al 2 O 3 Precursor, γ-Al 2 O 3 Al 2 O 3 -mx, where m is 1g of γ-Al 2 O 3 The value of the volume of the corresponding hydrophobic group, x is the hydrophobic modifier used (dimethyldiethoxysilane, propyltrimethoxysilane, octyltrimethoxysilane, etc.).

[0015] Furthermore, the wet impregnation method for Cu-ZnO loading in step S3 specifically includes: taking copper nitrate trihydrate Cu(NO 3 )·3H 2 O and zinc nitrate hexahydrate Zn(NO 3 )·6H 2 O, pour into 10ml deionized water, stir for 3h until completely dissolved, and mix the solution evenly; take γ-Al 2 O3 The powder is immersed in the above solution and stirred continuously until the liquid in the beaker is almost completely volatilized. After drying and calcination, a hydrophobic supported catalyst is obtained. 2 O 3 Samples loaded on (Cu-ZnO) y / Al 2 O 3 It shows that the hydrophobically modified γ-Al 2 O 3 The sample loaded on the z ) y / Al 2 O 3 -mx(y represents the proportion of Cu to Al 2 O 3 When the ZnO content is 0, only Cu is used. y / Al 2 O 3 or Cu y / Al 2 O 3 -mx means.

[0016] Furthermore, the mass of the supported Cu is related to the 2 O 3 The mass ratio of ZnO and Cu is (1-3):10, among which the mass ratio of ZnO and Cu is (0-10):10.

[0017] Furthermore, the drying temperature is 60°C, and the drying time is 8 to 24 hours; the calcination conditions are: increasing the temperature to 350°C at a rate of 5°C / min, and calcining for 3 hours;

[0018] Furthermore, the easy impregnation-capture method for Cu-ZnO loading in step S3 specifically includes: using copper nitrate trihydrate (Cu(NO 3 ) 2 ·3H 2 O, SigmaAldrich) and zinc nitrate hexahydrate (Zn(NO 3 ) 2 6H 2 O, SigmaAldrich) as the source of copper and zinc oxide. 2 O 3The precursor is placed in water and ethanol and ultrasonicated for 2-3 hours. Prepare copper nitrate and zinc nitrate solutions, and drop the former to ensure that the loading amount of this method is the same as that of the wet impregnation method. The mixed solution is stirred at room temperature. After centrifugal washing twice, the sample powder is placed in a vacuum drying oven for drying. Calcination at 350°C for 3 hours at a heating rate of 5°C / min to obtain a hydrophobic supported catalyst. Samples loaded using this method are indicated by adding "-s" at the end of the name.

[0019] Furthermore, γ-Al 2 O 3 The amount of precursor and anhydrous ethanol is 0.8-1.2 g; 240-360 mL; the concentration of the copper nitrate trihydrate solution added is 1 mg / mL. The mass of the loaded Cu is related to the γ-Al 2 O 3 The mass ratio of ZnO to Cu is (1-3):10, among which the mass ratio of ZnO to Cu is (0-10):10.

[0020] On the other hand, the present invention proposes the application of the above method in the preparation of methanol by co-hydrogenation of carbon monoxide and carbon dioxide, which specifically includes: 2 O 3 The catalyst is first reduced at a temperature of 200-280°C, a pressure of atmospheric pressure, and a reducing gas volume percentage of 10% H 2 and 90% N 2 The mixture was reduced for 1-3h under the conditions of a space velocity of 9000-18000ml / (g·h), and then the evaluation reaction of carbon monoxide and carbon dioxide co-hydrogenation to methanol was carried out at a reaction temperature of 230-280°C, a reaction pressure of 3.0-5.0Mpa, a mass space velocity of 10000-24000ml / (g·h), and a mixture with different carbon monoxide, carbon dioxide and hydrogen volume ratios. The components of the mixed gas are: carbon monoxide accounts for 0-30% by volume, carbon dioxide accounts for 0-30% by volume, and the remaining volume is hydrogen.

[0021] Beneficial effects of the present invention:

[0022] Due to the γ-Al 2 O 3 Due to its availability, mechanical strength, acid-base properties, high surface area and well-developed porous structure, it is widely used as a carrier for heterogeneous catalysts in various processes, but γ-Al is rarely used in its use. 2 O 3 However, alumina has been shown to change structure under hydrothermal conditions, with a surface area loss of more than 70%. 2 In the hydrogenation reaction, γ-Al 2 O 3 It is in a high temperature and high pressure environment, accompanied by the production of by-product water, that such an environment will lead to the formation of γ-Al2 O 3 The structural collapse and surface property changes of the carrier will also lead to sintering of the supported metal, etc. Such phenomena will not only affect the efficiency of the catalytic reaction but also reduce the life of the catalyst.

[0023] By 2 O 3 The surface of the material is hydrophobically modified with methyl groups, and the catalyst surface becomes hydrophobic, which is more conducive to the desorption of byproduct water, thereby increasing the catalytic efficiency and extending the life of the catalyst. 2 O 3 The carrier and the loaded Cu will have an impact. First, hydrophobic modification is conducive to the positive reaction. Second, hydrophobic modification can reduce the γ-Al 2 O 3 The hydrothermal effect on the carrier makes γ-Al 2 O 3 The stability of the carrier is more durable. In addition, the hydrophobically modified γ-Al 2 O 3 The surface properties of the carrier will change, and the CO 2 The adsorption and activation capacity of γ-Al is improved. In addition, after hydrophobic treatment, the oxidation, aggregation and sintering of copper particles can be reduced, thereby maintaining the efficiency of the catalytic reaction. The improvement of hydrophobicity ensures that the catalyst can still maintain high activity under high humidity conditions, which is particularly important in the methanol production reaction. 2 O 3 The carrier is pretreated to improve the γ-Al 2 O 3 The disadvantage of the carrier's hydrophilicity, thereby increasing the CO / CO 2 Efficiency of hydrogenation to methanol.

[0024] γ-Al prepared by evaporation induced self-assembly (EISA) method 2 O 3 The carrier has a highly ordered mesoporous structure, which improves the accessibility and specific surface area of ​​the pores and provides a better physical and chemical environment for the loading of active components. The optimization of the pore structure not only facilitates the mass transfer and diffusion of reactants, but also plays a positive role in the rapid removal of products from the reaction zone. The high specific surface area and ordered mesoporous structure work together to ensure that the high-loaded active components can be effectively exposed to the reaction environment, thereby improving the overall catalytic efficiency.

[0025] The innovative application of wet impregnation and easy impregnation-capture methods enables the active components to be uniformly loaded on γ-Al 2 O 3The active metals are uniformly dispersed on the carrier surface to ensure high utilization of active metals. Cu and Cu-ZnO are crucial active sites in the methanol synthesis reaction. Uniform dispersion on the carrier surface can avoid the loss of active sites caused by metal aggregation. Precise control of the loading amount and distribution of active components not only improves the catalytic efficiency of a single active site, but also improves the stability and resistance to shedding of active components by optimizing the interaction with the carrier. The appropriate loading of active components combined with the characteristics of the hydrophobic carrier significantly enhances the performance of the catalyst.

[0026] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0028] Figure 1 Unmodified γ-Al 2 O 3 Schematic diagram of hydrophobic angle;

[0029] Figure 2 Cu 10 / Al 2 O 3 -0.4 propylene hydrophobic angle schematic diagram;

[0030] Figure 3 Cu 10 / Al 2 O 3 Schematic diagram of -0.4 octane hydrophobic angle;

[0031] Figure 4 H 2 - Schematic diagram of TPR map. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] The method for preparing a hydrophobic supported catalyst described in this embodiment comprises the following steps:

[0035] S1: P123 was dissolved in anhydrous ethanol, stirred evenly, and a certain amount of aluminum isopropoxide was added after adjusting the pH. After the solution was stirred into a gel state, it was dried, calcined, and sieved to obtain γ-Al with a mesoporous structure. 2 O 3 Precursor;

[0036] S2: The γ-Al obtained in step S1 is 2 O 3 The precursor is mixed with deionized water, stirred evenly at room temperature, and a hydrophobic modifier is added dropwise in a fume hood to form a mixed solution; after stirring evenly, the mixed solution is placed in a 60°C water bath and stirred; the mixed solution is mixed and stirred under the condition of a water bath, and after being fully mixed evenly, centrifuged and dried to obtain a γ-Al with a hydrophobic surface. 2 O 3 Catalyst carrier;

[0037] S3: hydrophobically modified γ-Al obtained in step S2 2 O 3 The precursor is mixed with copper nitrate trihydrate and zinc nitrate hexahydrate, and Cu-ZnO is loaded by a wet impregnation method or an easy impregnation-capture method to obtain a hydrophobic loaded catalyst.

[0038] Example 2

[0039] The Cu 10 / Al 2 O 3 The preparation method comprises the following steps:

[0040] (1) Weigh 0.3775 g of copper nitrate trihydrate Cu(NO 3 )·3H 2 O, pour into 5 ml of deionized water, stir for 3 h, until the copper nitrate is completely dissolved and the solution is mixed evenly.

[0041] (2) Weigh 1g of γ-Al 2 O 3 The powder was placed in the above solution and stirred continuously until the liquid in the beaker was almost completely evaporated, and then the sample was placed in a drying oven maintained at 60°C and dried for 12 hours;

[0042] (3) After drying, the sample was finely ground and calcined at 350°C at a heating rate of 5°C / min for 3 h. After calcination, the sample was ground again to obtain Cu 10 / Al 2 O 3 catalyst.

[0043] Example 3

[0044] The Cu 10 / Al 2 O 3 -s preparation method, comprising the following steps:

[0045] (1) Preparation of solution A: Weigh 0.3775 g of copper nitrate trihydrate, pour into 5 mL of deionized water, and stir until the copper nitrate is completely dissolved and the solution is mixed evenly;

[0046] (2) Prepare solution B: weigh 1 g of γ-Al 2 O 3 The powder was poured into a beaker containing 240 ml of anhydrous ethanol and ultrasonicated for 2 h to make the γ-Al 2 O 3 The powder is evenly dispersed in the solution;

[0047] (3) After the ultrasonic treatment of solution B is completed, solution A is poured into solution B and stirred at room temperature for 24 hours. After stirring, the solution is centrifuged at 8000 r / min for 15 minutes. Repeat the centrifugation step twice to achieve the washing effect. After centrifugation, the sample is placed in a vacuum drying oven maintained at 60°C and dried for 12 hours;

[0048] (4) After drying, the sample was finely ground and calcined at 350°C at a heating rate of 5°C / min for 3 h. After calcination, the sample was ground again to obtain Cu 10 / Al 2 O 3 -s catalyst.

[0049] Example 4

[0050] The Cu 10 / Al 2 O 3 -0.2 E (E represents dimethyldiethoxysilane) preparation method, comprising the following steps:

[0051] (1) Weigh 3 g of γ-Al 2 O 3 The powder was placed in a beaker containing 240 ml of deionized water and stirred at room temperature. Then 0.6 ml of dimethyldiethoxysilane was added dropwise and the mixed solution was stirred at room temperature for 30 min.

[0052] (2) After mixing evenly, place the above solution in a water bath at 60°C and stir, seal the beaker, and stir for 5 hours;

[0053] (3) After stirring, the sample was centrifuged at 3500 r / min for 10 min. After centrifugation, the sample was placed in a vacuum drying oven at 60°C and dried for 12 h to obtain the hydrophobically modified Al 2 O 3 -0.2E (E represents dimethyldiethoxysilane)

[0054] (4) Weigh 0.755 g of copper nitrate trihydrate Cu(NO 3 )·3H 2 O, pour into 5 ml of deionized water, stir until the copper nitrate is completely dissolved and the solution is mixed evenly.

[0055] (5) Weigh 1g of γ-Al 2 O 3 The powder was placed in the above solution and stirred continuously until the liquid in the beaker was almost completely evaporated, and then the sample was placed in a drying oven maintained at 60°C and dried for 12 hours;

[0056] (6) After drying, the sample was finely ground and calcined at 350°C at a heating rate of 5°C / min for 3 h. After calcination, the sample was ground again to obtain Cu 10 / Al 2 O 3 -0.2 Ethyl (Ethyl represents dimethyldiethoxysilane) catalyst.

[0057] Example 5

[0058] The Cu 10 / Al 2 O 3 -0.2E-S (E represents dimethyldiethoxysilane) preparation method, comprising the following steps:

[0059] (1) Weigh 3 g of γ-Al 2 O 3 Powder, put into a beaker with 240ml deionized water, add 0.6mL dimethyldiethoxysilane, stir at room temperature for 30mins

[0060] (2) After stirring evenly, the solution was placed in a water bath at 60°C and stirred for 5 h.

[0061] (3) After stirring, the sample was centrifuged at 3500 r / min for 5 min, and repeated three times. After centrifugation, the sample was placed in a vacuum drying oven at 60°C and dried for 12 h to obtain the hydrophobically modified Al 2 O 3 -0.2Ethyl-s (x is ethyl, representing dimethyldiethoxysilane)

[0062] (4) Preparation of solution A: Weigh 0.3775 g of copper nitrate trihydrate, pour into 5 mL of deionized water, and stir until the copper nitrate is completely dissolved and the solution is mixed evenly;

[0063] (5) Prepare solution B: weigh 1 g of γ-Al 2 O 3 The powder was poured into a beaker containing 240 ml of anhydrous ethanol and ultrasonicated for 2 h to make the γ-Al 2 O 3 The powder is evenly dispersed in the solution;

[0064] (6) After the ultrasonic treatment of solution B is completed, solution A is poured into solution B and stirred at room temperature for 24 hours. After stirring, the solution is centrifuged at 8000 r / min for 15 minutes. Repeat the centrifugation step twice to achieve the washing effect. After centrifugation, the sample is placed in a vacuum drying oven maintained at 60°C and dried for 12 hours;

[0065] (7) After drying, the sample was finely ground and calcined at 350°C at a heating rate of 5°C / min for 3 h. After calcination, the sample was ground again to obtain Cu 10 / Al 2 O 3 -0.2 Ethyl-S (Ethyl represents dimethyldiethoxysilane) catalyst.

[0066] Example 6

[0067] The Cu 10 / Al 2 O 3 -0.4 propyl (x is propyl, representing propyltrimethoxysilane) preparation method, comprising the following steps:

[0068] (1) Weigh 3 g of γ-Al 2 O 3 Powder, put into a beaker with 240ml deionized water, add 1.2mL propyltrimethoxysilane, stir at room temperature for 30mins

[0069] (2) After stirring evenly, the solution was placed in a water bath at 60°C and stirred for 5 h.

[0070] (3) After stirring, the sample was centrifuged at 3500 r / min for 5 min, and repeated three times. After centrifugation, the sample was placed in a vacuum drying oven at 60°C and dried for 12 h to obtain the hydrophobically modified Al 2 O 3 -0.4C;

[0071] (4) Weigh 0.3775 g of copper nitrate trihydrate Cu(NO 3 )·3H 2 O, pour into 5 ml of deionized water, stir until the copper nitrate is completely dissolved and the solution is mixed evenly.

[0072] (5) Weigh 1g of modified γ-Al 2 O 3 The powder was placed in the above solution and stirred continuously until the liquid in the beaker was almost completely evaporated, and then the sample was placed in a drying oven maintained at 60°C and dried for 12 hours;

[0073] (6) After drying, the sample was finely ground and calcined at 350°C at a heating rate of 5°C / min for 3 h. After calcination, the sample was ground again to obtain Cu 10 / Al 2 O 3 -0.4 propane catalyst.

[0074] Example 7

[0075] The Cu 10 / Al 2 O 3 -0.4 octyl (x is octyl, representing octyltrimethoxysilane) preparation method, comprising the following steps:

[0076] (1) Weigh 3 g of γ-Al 2 O 3 The powder was placed in a beaker containing 240 ml of deionized water, 12 ml of octyltrimethoxysilane was added dropwise, and stirred at room temperature for 30 min;

[0077] (2) After stirring evenly, the solution was placed in a water bath at 60°C and stirred for 5 h.

[0078] (3) After stirring, the sample was centrifuged at 3500 r / min for 5 min, and repeated three times. After centrifugation, the sample was placed in a vacuum drying oven at 60°C and dried for 12 h to obtain the hydrophobically modified Al 2 O 3 -0.4 xin;

[0079] (4) Weigh 0.3775 g of copper nitrate trihydrate Cu(NO 3 )·3H 2 O, pour into 5 ml of deionized water, stir until the copper nitrate is completely dissolved and the solution is mixed evenly.

[0080] (5) Weigh 1g of modified γ-Al 2 O3 The powder was placed in the above solution and stirred continuously until the liquid in the beaker was almost completely evaporated, and then the sample was placed in a drying oven maintained at 60°C and dried for 12 hours;

[0081] (6) After drying, the sample was finely ground and calcined at 350°C at a heating rate of 5°C / min for 3 h. After calcination, the sample was ground again to obtain Cu 10 / Al 2 O 3 -0.4 octane catalyst.

[0082] Example 8

[0083] The catalysts prepared in Examples 2-7 were subjected to CO 2 The performance evaluation of hydrogenation to methanol was carried out as follows: 0.2 g of the above catalyst with a particle size of 20-40 was weighed, diluted with quartz sand of the same particle size at a ratio of 1:3 (V / V), loaded into the isothermal zone of the fixed bed reactor, and 10 vol% H2O2 was introduced at a flow rate of 60 ml / min. 2 +90vol%N 2 The reducing gas was reduced at 300 °C for 1 h, and then cooled to room temperature. H 2 :CO 2 The performance of carbon dioxide hydrogenation to methanol was measured under the conditions of a reaction gas volume ratio of 3:1, a pressure of 4 MPa, a space velocity of 12600 ml / (g·h) and a temperature of 250°C. The results are shown in the following table.

[0084] Methanol selectivity (%) Space-time yield (mmol / g·h) <h2 style=";text-align:left;direction:ltr"><![CDATA[Cu <h2 style=";text-align:left;direction:ltr"> 10 <h2 style=";text-align:left;direction:ltr"> / Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> 12.84 2.8438 <h2 style=";text-align:left;direction:ltr"><![CDATA[Cu <h2 style=";text-align:left;direction:ltr"> 10 <h2 style=";text-align:left;direction:ltr"> / Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> -s]]><h2 style=";text-align:left;direction:ltr"> 37.08 2.4693 <![CDATA[Cu 10 / Al 2 O 3 -0.2 Otsu]]> 54.33 4.2497 <![CDATA[Cu 10 / Al 2 O 3 -0.2Otsu-s]]> 75.62 3.9545 <![CDATA[Cu 10 / Al 2 O 3 -0.4 C 46 0.8859 <![CDATA[Cu 10 / Al 2 O 3 -0.4 Xin]]> 34.8 1.6638

[0085] With other conditions unchanged, only the temperature was raised to 270°C, and the test results are shown in the following table.

[0086] Methanol selectivity (%) Space-time yield (mmol / g·h) <h2 style=";text-align:left;direction:ltr"><![CDATA[Cu <h2 style=";text-align:left;direction:ltr"> 10 <h2 style=";text-align:left;direction:ltr"> / Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> 18.64 2.7758 <![CDATA[Cu 10 / Al 2 O 3 -0.4 C 53 4.8967

[0087] Example 9

[0088] The (Cu-ZnO 4 ) 10 / Al 2 O 3 The preparation method comprises the following steps:

[0089] (1) Weigh 0.3775 g of copper nitrate trihydrate Cu(NO 3 )·3H 2 O, and 0.146 g zinc nitrate hexahydrate Zu (NO 3 )·6H 2 O. Pour both into 5 ml of deionized water and stir until they are completely dissolved and the solution is mixed evenly.

[0090] (2) Weigh 1g of γ-Al 2 O 3 Powder, put into the above solution, continue stirring until the liquid in the beaker is almost completely evaporated, then put the sample into a drying oven maintained at 60°C and dry for 12 hours;

[0091] (3) After drying, the sample was finely ground and calcined at 350°C at a heating rate of 5°C / min for 3 h. After calcination, the sample was ground again to obtain (Cu-ZnO 4 ) 10 / Al 2 O 3 catalyst.

[0092] Example 10

[0093] The (Cu-ZnO 4 ) 10 / Al 2 O 3 -0.2 octyl (octyl represents octyltrimethoxysilane) preparation method, comprising the following steps:

[0094] (1) Weigh 3 g of γ-Al 2 O 3 The powder was placed in a beaker containing 240 ml of deionized water, and 6 ml of octyltrimethoxysilane was added dropwise, and stirred at room temperature for 30 min;

[0095] (2) After stirring evenly, the solution was placed in a water bath at 60°C and stirred for 5 h.

[0096] (3) After stirring, the sample was centrifuged at 3500 r / min for 5 min, and repeated three times. After centrifugation, the sample was placed in a vacuum drying oven at 60°C and dried for 12 h to obtain the hydrophobically modified Al 2 O 3 -0.2 xin;

[0097] (4) Weigh 0.3775 g of copper nitrate trihydrate Cu(NO 3 )·3H 2 O, and 0.146 g zinc nitrate hexahydrate Zu (NO 3 )·6H 2 O. Pour both into 5 ml of deionized water and stir until they are completely dissolved and the solution is mixed evenly.

[0098] (5) Weigh 1g of modified γ-Al 2 O 3Powder, put into the above solution, continue stirring until the liquid in the beaker is almost completely evaporated, then put the sample into a drying oven maintained at 60°C and dry for 12 hours;

[0099] (6) After drying, the sample was finely ground and calcined at 350°C at a heating rate of 5°C / min for 3 h. After calcination, the sample was ground again to obtain (Cu-ZnO 4 ) 10 / Al 2 O 3 -0.2 octane catalyst.

[0100] Example 11

[0101] The catalysts prepared in Examples 9-10 were subjected to CO / CO 2 The performance evaluation of methanol production by co-hydrogenation is as follows: 2g of pelletized catalyst (20-40 mesh) is weighed and mixed with 10g of 20-40 mesh quartz sand and loaded into a reaction tube. The mixture is reduced for 2h at 280℃ and normal pressure in an industrial hydrogen atmosphere, with a heating rate of 10℃ / min and a gas flow rate of 67.5mL / min. After the reduction is completed, the temperature drops to room temperature and the reaction gas is switched. The reaction pressure is 3Mpa, the reaction temperature is 250℃, the gas flow rate is 100mL / min, and the volume ratio of the mixed gas is 16.8% CO and 16.8% CO. 2 The proportion is 16.8%, and the rest is hydrogen. Under this condition, the performance of carbon dioxide hydrogenation to methanol was measured, and the results are shown in the following table.

[0102] sample Carbon conversion rate (%) Methanol selectivity (%) <h2 style=";text-align:left;direction:ltr"><![CDATA[(Cu-ZnO <h2 style=";text-align:left;direction:ltr"> 4 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> 10 <h2 style=";text-align:left;direction:ltr"> / Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> 26.52 66.63 <![CDATA[(Cu-ZnO 4 ) 10 / Al 2 O 3 -0.2 octyl]]> 25.68 75.42

[0103] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a hydrophobic supported catalyst, characterized in that: The following steps are involved: S1: P123 is dissolved in anhydrous ethanol, stirred evenly, and a certain amount of aluminum isopropoxide is added after adjusting the pH. After the solution is stirred into a gel state, it is dried, calcined, and sieved to obtain a γ-Al2O3 precursor with a mesoporous structure; S2: Mix the γ-Al2O3 precursor obtained in step S1 with deionized water, stir evenly at room temperature, and drop a hydrophobic modifier in a fume hood to form a mixed solution; after stirring evenly, place the mixed solution in a 60°C water bath and stir; mix and stir the mixed solution in a water bath, and after fully mixing evenly, centrifuge and dry to obtain a γ-Al2O3 precursor with a hydrophobic surface; S3: The hydrophobically modified γ-Al2O3 precursor obtained in step S2 is mixed with copper nitrate trihydrate, and copper is loaded by wet impregnation method or easy impregnation-capture method to obtain a hydrophobic loaded catalyst.

2. The method for preparing a hydrophobic supported catalyst according to claim 1, wherein: The step S1 specifically includes: synthesizing a highly ordered mesoporous γ-Al2O3 carrier by using an evaporation-induced self-assembly method, stirring pluronic P123 in an ethanol solvent for 3 hours, then slowly dripping a concentrated nitric acid solution to make the solution acidic, and continuing to stir at room temperature for 3 hours. Then, aluminum isopropoxide is added to the above solution, and vigorously stirred at room temperature until the solution is in a gel state. The mixed gel solution is placed in a 60°C oven and dried for 48 hours to turn the gel solution into white granules. After the sample is finely ground, it is placed in a muffle furnace for calcination, and when the sample cools to room temperature, the sample is ground.

3. The method for preparing a hydrophobic supported catalyst as claimed in claim 2, wherein: The amount of P123 used is 4-8 g; the amount of anhydrous ethanol used is 80-160 mL; the amount of aluminum isopropoxide used is 0.05-0.07 mol.

4. The method for preparing a hydrophobic supported catalyst as claimed in claim 2, wherein: The calcination conditions are: in an air environment, the temperature is increased to 400° C. at a heating rate of 1° C. / min for 4 hours, and the temperature is increased to 800° C. at a heating rate of 5° C. / min for 1 hour.

5. The method for preparing a hydrophobic supported catalyst according to claim 1, wherein: The step S2 specifically includes: placing 1-3g of γ-Al2O3 precursor into a beaker filled with 240ml of deionized water, dropping a certain amount of hydrophobic modifier, and stirring at room temperature for 30 minutes to evenly disperse the γ-Al2O3 particles; stirring for 5 hours in a water bath at 60°C, and during stirring, the beaker mouth should be sealed to prevent water vapor from entering; after stirring, centrifuging the solution at a speed of 3500r / min, and washing the carrier three times with anhydrous ethanol; after centrifugation, filtering the supernatant, and drying the powder in a 60°C oven for 24 hours to obtain a hydrophobically modified γ-Al2O3 precursor.

6. The method for preparing a hydrophobic supported catalyst according to claim 5, wherein: Hydrophobic modification agents include, but are not limited to, propyltrimethoxysilane, octyltrimethoxysilane, hexadecyltrimethoxysilane.

7. The method for preparing a hydrophobic supported catalyst according to claim 1, wherein: The step S3 of using the wet impregnation method to load copper specifically includes: Take copper nitrate trihydrate Cu(NO3)·3H2O and zinc nitrate hexahydrate Zn(NO3)·6H2O, pour them into deionized water, stir for 3 hours until the copper nitrate is completely dissolved and the solution is evenly mixed; take the hydrophobically modified γ-Al2O3 precursor and immerse it in the above solution, continue stirring until the liquid in the beaker is almost completely evaporated, and after drying and calcination, a hydrophobic supported catalyst is obtained.

8. The method for preparing a hydrophobic supported catalyst as claimed in claim 7, characterized in that: The mass ratio of the loaded Cu to the mass ratio of γ-Al2O3 is (1-3):10, wherein the mass ratio of ZnO to Cu is (0-10):10; the drying temperature is 60°C, and the drying time is 8-24h; the calcination conditions are: increasing the temperature to 350°C at a rate of 5°C / min, and calcining for 3h.

9. The method for preparing a hydrophobic supported catalyst according to claim 1, wherein: The easy impregnation-capture method for copper loading in step S3 specifically includes: placing 0.8-1.2 g of hydrophobically modified γ-Al2O3 precursor in 240-360 mL of anhydrous ethanol and ultrasonicating for 2-3 hours; preparing a copper nitrate solution and a zinc nitrate solution, dripping the former, and the ratio of the mass of the loaded Cu to the mass of γ-Al2O3 is (1-3):10, wherein the mass ratio of ZnO to Cu is (0-10):

10. The mixed solution was stirred at room temperature. After centrifugal washing twice, the sample powder was placed in a vacuum drying oven for drying. The sample powder was calcined at 350°C for 3 h at a heating rate of 5°C / min to obtain a hydrophobic supported catalyst.

10. Application of the method according to any one of claims 1 to 9 in the co-hydrogenation of carbon monoxide and carbon dioxide to produce methanol, characterized in that: The prepared γ-Al2O3 catalyst is first reduced for 1-3h under the conditions of a reduction temperature of 200-280°C, a pressure of normal pressure, a reduction gas volume percentage of 10% H2 and 90% N2 mixed gas, and a space velocity of 9000-18000ml / (g·h), and then an evaluation reaction of carbon monoxide and carbon dioxide co-hydrogenation to methanol is carried out in a mixed gas with different carbon monoxide, carbon dioxide and hydrogen volume ratios at a reaction temperature of 230-280°C, a reaction pressure of 3.0-5.0Mpa, a mass space velocity of 10000-24000ml / (g·h). The components of the mixed gas are: carbon monoxide accounts for 0-30% by volume, carbon dioxide accounts for 0-30% by volume, and the remaining volume is hydrogen.

Citation Information

Patent Citations

  • Catalyst for synthesizing methanol by hydrogenating carbon dioxide, preparation method and application thereof

    CN101757943A

  • Hydrophobic catalyst for synthesizing methanol through carbon dioxide hydrogenation and preparation method and application of hydrophobic catalyst

    CN112588320A

  • Method for preparing methanol through CO2 hydrogenation

    CN114920623A

  • Catalysts for methanol synthesis and method for their production

    US4349464A

  • A method of obtaining hydrocarbons from carbon dioxide

    WO2007012150A1